Use of dipeptidyl peptidase‐4 inhibitors and risk of splanchnic vein thrombosis: A Danish nationwide new‐user active comparator cohort study. Issue 2 (26th November 2020) - Pottegård, Anton; Lund, Lars Christian; Henriksen, Daniel Pilsgaard; Folkestad, Lars; Hellfritzsch, Maja; Hallas, Jesper; Kristensen, Kasper Bruun
Abstract: Use of dipeptidyl peptidase‐4 (DPP‐4) inhibitors, on the basis of spontaneous adverse event reports, has recently been suspected of causing splanchnic vein thrombosis. Here, we report the results of a population‐based new‐user active comparator cohort study addressing this hypothesis, comparing DPP‐4 inhibitor initiators (n = 75 042) with initiators of glucagon‐like‐peptide‐1 receptor agonists (GLP‐1RAs) or sodium‐glucose co‐transporter‐2 (SGLT2) inhibitors (n = 38 718). We estimated the hazard ratio (HR) associating DPP‐4 inhibitor use with risk of splanchnic vein thrombosis using Cox regression. In a crude analysis, the incidence rate of splanchnic vein thrombosis was 0.22/1000 person‐years among DPP‐4 inhibitor initiators, compared to 0.17 among GLP‐1RA/SGLT2 inhibitor initiators, corresponding to an unadjusted absolute incidence rate difference of 0.05 (95% confidence interval [CI] –0.04 to 0.14) and an HR of 1.29 (95% CI 0.78 to 2.15). Adjusting for potential confounders using stabilized inverse probability of treatment weighing, we obtained an absolute incidence rate difference of 0.03/1000 person‐years (95% CI –0.07 to 0.14) and an HR of 1.18 (95% CI 0.62 to 2.26). No evidence of increased risk of splanchnic vein thrombosis was found in supplementary analyses, including an absence of any dose–response patterns. As such, we found no association between DPP‐4 inhibitor use and splanchnic vein thrombosis risk.